Mathematics in economics and business studies - Apynis, Antanas; Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2002)
The books in microeconomics and macroeconomics are considered in view of mathematics consepts. The syllabus of mathematics for economics and business students is presented.